Immune landscape and immunotherapy for penile cancer - Tang, Yaxiong; Hu, Xu; Wu, Kan; Li, Xiang (Frontiers in Immunology, 2022)
Penile cancer is a rare malignancy and usually refers to penile squamous cell carcinoma (PSCC), which accounts for more than 95% of all penile malignancies. Although organ-sparing surgery is an effective treatment for early-stage PSCC, surgical intervention alone is often not curative for advanced PSCC with metastases to the inguinal and/or pelvic lymph nodes; thus, systemic therapy is required (usually platinum-based chemotherapy and surgery combined). However, chemotherapy for PSCC has proven to be of limited efficacy and is often accompanied by high toxicity, and patients with advanced PSCC usually have poor prognosis. The limited treatment options and poor prognosis indicate the unmet need for advanced PSCC. Immune-based therapies have been approved for a variety of genitourinary and squamous cell carcinomas but are rarely reported in PSCC. To date, several studies have reported high expression of PDL1 in PSCC, supporting the potential application of immune checkpoint inhibitors in PSCC. In addition, human papillomavirus (HPV) infection is highly prevalent in PSCC and plays a key role in the carcinogenesis of HPV-positive PSCC, suggesting that therapeutic HPV vaccine may also be a potential treatment modality. Moreover, adoptive T cell therapy (ATC) has also shown efficacy in treating advanced penile cancer in some early clinical trials. The development of new therapeutics relies on understanding the underlying biological mechanisms and processes of tumor initiation, progression and metastasis. Therefore, based on the interest, we reviewed the tumor immune microenvironment and the emerging immunotherapy for penile cancer.